Monster needs your vote - Czajak, Paul (A Monster & me book, 2015)
"Election season is here and Monster is ready to vote! But why cast your ballot when you can run for president instead? With speeches, debates, and a soapbox or two, Monster's newest tale is a campaign encouraging kids to take a stand and fight for what they believe in"--